2012
DOI: 10.1016/j.humimm.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

In contrast to HIV, KIR3DS1 does not influence outcome in HTLV-1 retroviral infection

Abstract: While most carriers of human T-cell leukemia virus type 1 (HTLV-1) remain asymptomatic throughout their lifetime, infection is associated with the development of adult T cell leukemia (ATL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). The exact parameters that determine these outcomes are unknown but are believed to include host genetic factors that control the immune response to infection. Host response to fellow retroviridae member HIV is influenced by the expression of members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…iKIR "rescuing" of activated CD8 + T cells may be particularly important in this setting. Most KIR-HLA genetic associations are not replicated across viral infections, for example, KIR3DS1 with HLA-Bw4 is pro-tective in the context of HIV-1 but not HTLV-1 (56); this is difficult to understand unless a very strong peptide dependence is postulated. In contrast, we report that all iKIRs enhance HLA class I associations in all three persistent virus infections we have studied (HIV-1, HCV, and HTLV-1), which suggests a universality that is often missing from KIR studies.…”
Section: Discussionmentioning
confidence: 99%
“…iKIR "rescuing" of activated CD8 + T cells may be particularly important in this setting. Most KIR-HLA genetic associations are not replicated across viral infections, for example, KIR3DS1 with HLA-Bw4 is pro-tective in the context of HIV-1 but not HTLV-1 (56); this is difficult to understand unless a very strong peptide dependence is postulated. In contrast, we report that all iKIRs enhance HLA class I associations in all three persistent virus infections we have studied (HIV-1, HCV, and HTLV-1), which suggests a universality that is often missing from KIR studies.…”
Section: Discussionmentioning
confidence: 99%
“…The role of KIR3DS1 has also been investigated in other viral infections such as human T-cell leukemia virus type 1 (HTLV-1), H1N1 influenza A, and hepatitis B virus infection (HBV). While no evidence for the participation of KIR3DS1 in control of HTLV-1 infection was found ( O’Connor et al, 2012 ), carriage of KIR3DS1 and other haplotype B containing KIRs was associated with severe pandemic influenza A (H1N1) 2009 infections ( Aranda-Romo et al, 2012 ). Frequencies of KIR3DS1 as well as KIR2DS1 and KIR2DL5 were furthermore increased in a group of patients who spontaneously recovered from HBV compared to individuals with chronic HBV infection or healthy controls ( Zhi-Ming et al, 2007 ).…”
Section: Role Of the Kir3ds1 In Diseasesmentioning
confidence: 99%
“…In contrast, other studies found no association between polymorphisms in HLA and KIR alleles with HTLV-1 infection. Although KIR3DS1 expression has been associated with host response in HIV infection, KIR3DS1-mediated regulation on HTLV-1 infection does not occur or is ineffective [46]. Likewise, other polymorphisms in the HLA-C and KIR alleles were also not associated with the risk of progressing to HAM [43].…”
Section: Htlv-1 Infected Subjects’ Immunogenetic Profilementioning
confidence: 99%